THE USE OF THE SYNTHETIC ANALOGUE OF LEUCIN-ENCEPHALINE IN COMPLEMENTARY THERAPY OF DOGS WITH CHRONIC PANCREATITIS - A. G. Milastnaia (Ukrainian Journal of Veterinary Sciences, 2020)
A review of the problem of treating dogs for pancreatitis with peptide drugs is presented. The main attention is paid to the analysis of the use of somatostatin, octreotide and the synthetic analogue of leucine-enkephalin – dalargin. Despite numerous studies of the therapeutic effects of these agents for acute pancreatitis and pancreatic necrosis in humane medicine, there is no definitive answer about their efficacy in dogs due to the lack of work performed in accordance with the criteria of evidence-based medicine. The use of dalargin in the complex therapy of dogs with chronic pancreatitis, eliminates or reduces pain and dyspeptic phenomena, contributes to the onset of positive changes at the same time a number of positive changes in the functional state of the pancreas manifested by decreased serum amylase activity 3 times, pancreatic lipase in the 1,9 times. Studies carried out on dogs, patients with chronic pancreatitis, it is determined that against the background of treatment of synthetic analogue Leukin-enkefaline – Dalagin. The intensity of pain decreased (up to 5 days in 90% of patients), decreased amylase and pancreatic lipase activity and TBK-active product (malonic dialdehyde, MDA) in their blood serum. Ultrasound showed data on the reduction of pancreatic edema, in 7 sick dogs, its sizes were restored to indicators in healthy animals